Novel Silicon Titanium Diboride Micropatterned Substrates for Cellular Patterning. (June 2020) - Friguglietti, Jefferson; Das, Susmi; Le, Phi; Fraga, Daniel; Quintela, Marcos; Gazze, Salvatore A.; McPhail, Darius; Gu, Jianhua; Sabek, Omaima; Gaber, A. Osama; Francis, Lewis W.; Zagozdzon-Wosik, Wanda; et al.
Abstract: Both hard material photolithography and soft lithography are widely used for patterned cell culture. Soft lithography techniques enable bioactive molecule incorporation, however complex surface modifications are required to introduce specific ligands or proteins in conventional photolithography. In this study, we demonstrate human umbilical vein cell (HUVEC) and adult bone marrow derived mesenchymal stem cell (MSC) patterning on titanium diboride (TiB2 ) layers deposited on silicon (Si) substrates by electron-beam evaporation and micropatterned using photolithography. Micropatterned cell growth specificity on geometric shapes of circle and/or lines is achieved via differential growth factors adsorption in the presence of heparin. Specifically, the deposited films of TiB2 showed increased stiffness, hardness, hydrophilicity and surface charge when compared to background Si. These substrates were found to be compatible with HUVEC and MSC viability, based on biomarker expression and RNA-sequence transcriptome analysis. Cell-type dependent, micropattern selective cell growth, such as contact guidance, alignment, and durotaxis, were observed. In addition, MSC clustering was achieved, enabling a three-dimensional (3D) aggregate based microenvironment during culture. This study clearly demonstrates the potential of microfabricated Si and TiB2 biomaterials for patterned cell culture in vitro, independent of any additional surface modification.